INVESTIGATING THE CHEMICAL PROPERTIES, THERMAL AND MICROSTRUCTURAL CHARACTERIZATIONS OF INDUSTRIAL WASTE BASED ASPHALT CONCRETE FOR ENHANCED PERFORMANCE (Nigerian Journal of Technology, 2025)
This research addresses the growing need for sustainable alternatives in road construction by investigating the use of industrial waste materials specifically steel slag and fly ash as partial replacements for natural aggregates in asphalt concrete. The problem lies in the environmental impact of quarrying natural aggregates and the under-utilization of industrial by-products, which pose disposal challenges. To explore this, steel slag and fly ash were incorporated into asphalt mixtures at varying replacement levels (2%, 4%, 6%, and 8%) to assess their suitability as substitutes. The methodology involved characterizing the materials using physical tests (Aggregate Impact Value, Aggregate Crushing Value, and penetration tests), as well as chemical and thermal analyses (X-ray diffraction, X-ray fluorescence, and thermogravimetric analysis). The mechanical properties of the modified asphalt were evaluated through Marshall Stability and flow tests to measure strength and deformation under load. Results show that the inclusion of steel slag and fly ash significantly enhanced the stability and durability of asphalt concrete, with optimal performance observed at 6% replacement. This study concludes that these industrial waste materials can serve as sustainable alternatives in asphalt production, reducing environmental impacts while meeting road construction standards in Nigeria.